2022
DOI: 10.1002/jez.2661
|View full text |Cite
|
Sign up to set email alerts
|

Does atrazine induce changes in predator recognition, growth, morphology, and metamorphic traits of larval skipper frogs (Euphlyctis cyanophlyctis)?

Abstract: Atrazine, an info disruptor, interferes with the olfaction of aquatic organisms by impairing the chemosensory system. Consequently, it affects behavior, physiology, and growth increases mortality and infections, and suppresses the immune system of aquatic animals. In this study, we wanted to determine the sensitivity of larval Euphlyctis cyanophlyctis to different concentrations of atrazine by assessing their antipredator behavior, growth, morphology, and metamorphic traits. The results indicate that exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 102 publications
(203 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated that atrazine can disrupt endocrine function in both wildlife and humans, potentially leading to reproductive and developmental problems. In animals such as fish and amphibians, atrazine exposure has been linked to hormonal imbalances and reproductive issues [37].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that atrazine can disrupt endocrine function in both wildlife and humans, potentially leading to reproductive and developmental problems. In animals such as fish and amphibians, atrazine exposure has been linked to hormonal imbalances and reproductive issues [37].…”
Section: Introductionmentioning
confidence: 99%